TMEM97 ablation aggravates oxidant-induced retinal degeneration - Shen, Hongtao; Li, Jing; Heisler-Taylor, Tyler; Makin, Ryan; Yang, Huan; Mavlyutov, Timur A.; Gelfand, Bradley; Cebulla, Colleen M.; Guo, Lian-Wang (Cellular signalling, 2021)
The retinal pigment epithelium (RPE) is critical to the survival of the overlying photoreceptors. Subject to light exposure and active metabolism, the RPE and photoreceptors are particularly susceptible to oxidative damage that plays an important part in age-related macular degeneration (AMD). Recent meta-analyses identified TMEM97 as a new putative AMD risk locus, though it is yet to be functionally verified. The role of TMEM97 in the retina and RPE is not known. Here we investigated TMEM97 function using the sodium iodate model of oxidant-induced retinal degeneration in TMEM97 knockout (KO) mice. We found markedly increased reactive oxygen species (ROS) and loss of photoreceptos in TMEM97 KO mouse retinas relative to wild type (WT) controls. In vitro, sodium iodate treatment of CRISPR-mediated TMEM97 KO RPE cells resulted in diminished abundance of the master antioxidant transcription factor NRF2 and its target gene product SOD2, the mitochondrial superoxide dismutase, as well as elevated ROS and apoptosis markers. Moreover, TMEM97 KO affected proteins key to mitochondrial and lysosomal stability and impeded autophagy flux. These findings suggest that the absence of TMEM97 in RPE cells disturbs redox-balancing systems, thereby heightening oxidative stress. As TMEM97 is a druggable target, this study may inspire interest in basic and translational research in the context of retinal degeneration. •Knockout of TMEM97, a putative AMD risk locus, exacerbates oxidant-induced RPE damage and photoreceptor loss in mice.•TMEM97 knockout in oxidant-treated ARPE19 cells decreases NRF2 and SOD2 proteins while heightening ROS and apoptosis.•TMEM97 knockout also affects mitochondria, lysosomes, and autophagy flux in oxidant-treated ARPE19 cells.•TMEM97 is now known as a drug target and could be a candidate for clinical translation to treat retinal diseases.